Perspectives in cosmetic dermatology: What is in front of the mirror? (2018)
Managing patient expectations can be a difficult task and is one that cosmetic dermatologists frequently encounter. Misinformation and unrealistic expectations can oftentimes exist regarding cosmetic procedures and their results. These misconceptions can result in patient dissatisfaction and frustration on the physician's behalf. This case report underscores the importance of utilizing what is arguably the most basic and ancient tool in the office, the mirror. There are many different facets to the patient encounter and a variety of devices at the physician's disposal. Proper use of this valuable tool can improve communication, elucidate patient concerns, and reflect the focus on the patient. These can ultimately lead to improved procedure outcome and patient satisfaction. © 2018 Wiley Periodicals, Inc.